2022
DOI: 10.1039/d1cc06723k
|View full text |Cite
|
Sign up to set email alerts
|

Near-infrared vapochromism in lipid-packaged mixed-valence coordination polymers

Abstract: Reversible vapochromism in the NIR region is achieved for a mixed-valence platinum complex with lipid counterions, from which exclusion of crystallization water by organic vapor alters lipid molecular orientation that...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Although not a focus of this work, in situ changes in the phonon mode can change the optical properties, and this concept can be applied to optical materials. [58][59] Every synthetic process was operated under air.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although not a focus of this work, in situ changes in the phonon mode can change the optical properties, and this concept can be applied to optical materials. [58][59] Every synthetic process was operated under air.…”
Section: Discussionmentioning
confidence: 99%
“…Ethylenediamine, HCl aq., H 2 O 2 , MnCl 2 ⋅ 4H 2 O were obtained from Wako pure chemical industries, Ltd. and used as received. [Pt(en) 2 ]Cl 2 and [PtCl 2 (en) 2 ]Cl 2 were synthesized following previously published methods [58–59] . Every synthetic process was operated under air.…”
Section: Methodsmentioning
confidence: 99%
“…Nagai et al reported that an assembly of an amphiphilic anion and an iodo-bridged chain of Pt complex exhibits reversible vapochromism upon exposure to methanol and water vapour. 9 The dehydration and hydration caused a change in the layered structure and the electronic state of the Pt complex. As described above, the combination of amphiphilic ions and metal complexes may enable the construction of assemblies in which the assembly structure and electronic state of the metal complexes change reversibly in response to external stimuli.…”
Section: Introductionmentioning
confidence: 99%